The effectiveness of pharmacist intervention in improving medication adherence in patients with chronic kidney disease: a randomized controlled trial - Okoro, Roland Nnaemeka; Ummate, Ibrahim; Ohieku, John David; Yakubu, Sani Ibn; Adibe, Maxwell Ogochukwu; Ummate, Ibrahim; Ohieku, John David; Yakubu, Sani Ibn; Adibe, Maxwell Ogochukwu (African Journal of Nephrology, 2023)
Background: Chronic kidney disease (CKD) is a global health concern associated with a high risk of cardiovascular disease, end-stage renal failure, and premature death. The interventions of pharmacists in chronic disease management have been promising. However, there is little evidence of their participation in managing CKD, particularly in developing countries. The objective of this study was to evaluate the influence of pharmacists’ interventions in improving medication adherence in patients with CKD. Methods: This double-arm randomised controlled study was carried out at the nephrology outpatient departments of two Nigerian hospitals. Patients with stage 1 to 4 CKD who visited the hospitals between November 2019 and February 2020 were enrolled. Pharmacists’ interventions included CKD education, dietary suggestions, medication adherence counselling, and telephonic consultations. The usual care (UC) group served as the control and received only ordinary hospital treatment, whereas the pharmaceutical care (PC) group received usual care in addition to pharmacists’ interventions. The influence of pharmacists’ engagement was assessed by recording improvements in adherence scores and creatinine levels after 6 and 12 months, respectively. Using standard statistics, the PC and UC groups were compared at the P < 0.05 significance level. Results: A total of 147 patients (74 in the UC and 73 in the PC group, respectively) completed the study. Baseline variables were comparable between the two groups. Pharmacists’ interventions achieved significant improvement in mean adherence scores at 12 months in the PC group compared to the UC group (0.2 ± 0.6 vs 0.7 ± 1.3, P = 0.003). Also, serum creatinine levels significantly improved in the intervention group compared to the control group at the end of the study (245.9 ± 101.7 µmol/L vs 291.7 ± 140.7 µmol/L, P = 0.025). In the adjusted analysis, participants in the PC group were 2.11 times (P = 0.038) more likely to achieve excellent medication adherence than their counterparts in the UC group. Conclusion: Our findings indicate that pharmacists’ interventions have the potential to improve medication adherence among patients with CKD.